The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.ijrobp.2007.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Tumor Volume is Predictive of Poor Overall and Progression-Free Survival: Secondary Analysis of the Radiation Therapy Oncology Group 93-11 Phase I-II Radiation Dose-Escalation Study in Patients with Inoperable Non–Small-Cell Lung Cancer

Abstract: Recommended CitationWerner-Wasik, Maria; Swann, R. Suzanne; Bradley, Jeffrey; Graham, Mary; Emami, Bahman; Purdy, James; and Sause, William, "Increasing tumor volume is predictive of poor overall and progressionfree survival: Secondary analysis of the Radiation Therapy Oncology Group 93-11 phase I-II radiation dose-escalation study in patients with inoperable non-small-cell lung cancer" (2008 Patients with non-small-cell lung cancer (NSCLC) in the Radiation Therapy Oncology Group (RTOG) 93-11 trial received ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 13 publications
6
44
1
Order By: Relevance
“…GTV1 before RT trended to be associated with OS in univariate analysis which amends current literature showing strong evidence for a prognostic significance of tumor volume detected before RT (13)(14)(15)(16)22) or chemotherapy of NSCLC (23). Koo et al (14) for instance reported a trend for inferior survival outcome in patients with poor tumor volume reduction during CCRT of Decrease Increase Total GTV1 to GTV2 Decrease 15 10 25 Increase 0 2 2 Total 15 12 27 OPN, osteopontin.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…GTV1 before RT trended to be associated with OS in univariate analysis which amends current literature showing strong evidence for a prognostic significance of tumor volume detected before RT (13)(14)(15)(16)22) or chemotherapy of NSCLC (23). Koo et al (14) for instance reported a trend for inferior survival outcome in patients with poor tumor volume reduction during CCRT of Decrease Increase Total GTV1 to GTV2 Decrease 15 10 25 Increase 0 2 2 Total 15 12 27 OPN, osteopontin.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, there is strong evidence in the literature that GTV is a potential prognostic factor in conformal RT of NSCLC (13)(14)(15)(16)21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][28][29][30][31][32]. The coupling between the tumor dynamics and the immune response is obtained mathematically by the product of two mechanisms.…”
Section: Biological Hypotheses and Mathematical Interpretationsmentioning
confidence: 99%